Mathematical model of failure the drives suspensions of the conveyor with suspended belt and distributed drive at break in the electric chain - Tolkachev E.N. (Научно-технический вестник Брянского государственного университета)
The article is devoted to the topical issue, which is related to simulation of the failures of drives suspensions of the conveyor with suspended belt and distributed drive. A mathematical model of the failure of individual drives of suspensions due to the breakage of the electric circuit has been developed. Dynamic characteristics of the basic version of a conveyor with suspended belt were simulated.